Lexical bundles in the discussion section moves of high impact medical research articles - Al-Shujairi, Yasir Bdaiwi Jasim; Tan, Helen; Abdullah, Ain Nadzimah; Nimehchisalem, Vahid; Lee, Geok Imm (Universiti Putra Malaysia Press, 2020)
Findings in medical research articles (MRAs), in particular, the discussion section interest not only the discourse community but also the ordinary people. Therefore, the writing needs to be comprehensible to both experts and laymen alike. To achieve a successful writing of a MRA, the author’s knowledge of lexical bundles (LBs) and rhetorical moves in MRAs are essential. Though research on rhetorical moves in RAs abounds, there is a lack of study that examines the LBs in the rhetorical moves in MRAs. This scarcity of research prompted this study to examine the LBs associated with the moves and steps in the discussion section of high impact MRAs. A total of 50 MRA discussion sections were investigated. Findings revealed that generally groups of LBs were related to the functions of the moves and steps in the discussion sections. The majority of LBs were associated with move Stating Research Conclusion (31%), move Contrasting Present and Previous Outcomes (23%) and move Explain Specific Research Outcomes (22%). The findings from this study can provide informed input not only to ESP writing instructors on how to navigate the writing of the discussion section in an RA but also to novice writers on how to follow the conventions of the discussion section in writing MRAs.